Dynamic spectral study of Pc 3-5 magnetic pulsations observed in the north polar cusp region - Kato, Yoshio; Tonegawa, Yutaka; Tomomura, Kiyoshi (1985)
P(論文) Dynamic spectral characteristics of magnetic pulsations in the frequency range from Pc 3 to Pc 5 are examined on the basis of simultaneous observations at Cambridge Bay in the north polar cusp region and Fort Smith in the auroral zone. Both stations are located at almost the same longitude. In the dynamic spectra observed at both stations two predominant spectral bands are generally seen in the frequency ranges of Pc 3 (20-80mHz) and Pc 4/5 (3-10mHz). Although spectral peaks in the Pc 3 and Pc 4/5 bands are shown at almost the same frequencies for both stations, sharpness (Q value) of the peaks is very different between the stations. The spectral peaks at Fort Smith are much sharper than those at Cambridge Bay. These observed features are discussed in the light of propagation and resonance mechanism of Pc 3 and Pc 4/5 waves in the magnetosphere. departmental bulletin paper